EXPERIMENTAL EVIDENCE FOR THE PRESSURE DEPENDENCE OF FISSION TRACK ANNEALING IN APATITE - Wendt A.S.; Vidal O.; Chadderton L.T. (My University, 2002)
Fission track analysis has seen a major expansion in application to general geological problems reflecting its advances in understanding the temperature dependence of track annealing and track length distributions. However, considerable uncertainties still persist, in particular concerning the stability of fission tracks subjected to the interaction of environmental physical parameters (e.g. pressure, temperature, stress) and in extrapolation of laboratory data to geological time scales. In this work, we studied the fading behavior of spontaneous fission tracks in basic apatite [hexagonal Ca5(PO4)3(OH, F, Cl)] when exposed simultaneously to laboratory pressures, temperatures and stress over varying time spans. The experiments showed that track fading is a complex recovery mechanism, which is extremely sensitive to the coupling of these three parameters. In particular, a strong decrease in the fission track fading rate was observed as a function of increasing pressure. And a nearly temperature-independent dramatic increase in fission track recovery was observed as a function of stress. Consequently, (1) the stability field of fission tracks in apatite increases towards temperatures higher than 110°C depending on the absolute pressure; (2) closure ages in apatite are underestimated (>100% for an ideal geothermobarometric gradient); (3) related exhumation and erosion rates are overestimated above the closure temperature and underestimated below the closure temperature; and (4) since the widely applied statistical description of thermally induced fading kinetics does not account for the influences of either pressure or stress and is based on fission track annealing data produced at ambient pressure, the accuracy in extrapolating fission track data to geological time scales and in their application to dynamical systems must be cast into doubt.